Solve the given trigonometry equation

In summary, the task involves finding the values of the variable that satisfy the specified trigonometric equation, which may require applying trigonometric identities, algebraic manipulation, and considering the periodic nature of trigonometric functions.
  • #1
chwala
Gold Member
2,767
395
Homework Statement
Find the exact value given the equation;

##\sinh^{-1} x = 2\cosh^{-1} (2)##
Relevant Equations
Trigonometry
In my approach i have the following lines

##\ln (x + \sqrt{x^2+1}) = 2\ln (2+\sqrt 3)##

##\ln (x + \sqrt{x^2+1} = \ln (2+\sqrt 3)^2##

##⇒x+ \sqrt{x^2+1} =(2+\sqrt 3)^2##

##\sqrt{x^2+1}=-x +7+4\sqrt{3}##

##x^2+1 = x^2-14x-8\sqrt 3 x + 56\sqrt 3 +97##

##1 = -14x-8\sqrt 3 x + 56\sqrt 3 +97##

##14x+8\sqrt 3 x = 96+56\sqrt 3##

##(14+8\sqrt 3)x = 96+56\sqrt 3##

##x= \dfrac{96+56\sqrt 3}{14+8\sqrt 3} = \dfrac{1344-768\sqrt 3 +784\sqrt 3-1344}{196-192}= \dfrac{16\sqrt 3}{4}=4\sqrt 3##

Bingo ...any insight or alternative approach is welcome.
 
Physics news on Phys.org
  • #2
Using the double angle formula looks easier:
$$x = \sinh(2\cosh^{-1}(2)) = 4\sinh(\cosh^{-1}(2)) = 4\sqrt{\cosh^2(\cosh^{-1}(2)) - 1} = 4\sqrt 3$$
 
  • Like
  • Informative
Likes chwala, MatinSAR and Orodruin
  • #3
Apply sinh:
$$
x = \sinh(2\cosh^{-1}(2))
= 2\sinh(\cosh^{-1}(2)) \cosh(\cosh^{-1}(2))
= 4\sinh(\cosh^{-1}(2))
$$
Since ##\sinh = \sqrt{\cosh^2-1}##
$$
\sinh(\cosh^{-1}(2)) = \sqrt{4-1} = \sqrt 3
$$
anf therefore
$$
x = 4\sqrt 3
$$

Edit: Cross posted with @PeroK - at least we said exactly the same …
 
  • Informative
  • Like
Likes chwala and MatinSAR
Back
Top